Kindy talk free workshop - Fatimah, Ali; Wan Jumani, Fauzi; Mardhiyyah, Zamani (2021)
5 June 2021- The Centre for Modern Languages’ Kindy Talk Team successfully organised a 3-hour free online workshop on Using Technology for Early Childhood Educators via Google Meet from 9 a.m. to 12 p.m. with 17 early childhood educators, many of whom are from Kuantan and 3 as far as from Selangor and Kelantan.